Descriptive Analysis of the Incidence of Suicide by Hanging at Bhayangkara Tk. 1 Pusdokkes Polri Hospital: A Review of Data from the Last Five Years and an Islamic Perspective - Afra Shamila Ambadar; Farah Primadani Kaurow; Siti Marhamah; Liko Maryudhiyanto (Green Publisher Indonesia, 2026)
Background: Suicide is a major global public health concern, with its incidence continuing to rise each year. Hanging remains one of the most frequently used methods, including in Indonesia. Forensic examination is crucial for identifying victim characteristics, determining causes and mechanisms of death, supporting legal processes, and contributing to prevention strategies. Objective: The objective of this study is to obtain a comprehensive picture of the characteristics of victims, the instruments used, the cause and mechanism of death, case management efforts, and an Islamic perspective on suicide cases by hanging. Methods: This study used a descriptive method with a cross-sectional design and a qualitative approach. Data were collected retrospectively from medical records of suicide victims by hanging examined at the Forensic Medicine Department of Bhayangkara Hospital Tk. 1 Pusdokkes Polri from 2020 to 2024. The analyzed variables included age, sex, wound characteristics, instruments used, and causes and mechanisms of death. The majority of victims were male and belonged to the productive age group, with rope being the most commonly used ligature. Results: Although several cases lacked detailed information on the mechanism of death, available data indicated that asphyxia due to neck compression was the primary cause. These findings align with forensic theory, which states that death in hanging cases typically results from obstruction of air and blood flow caused by pressure on neck structures. Conclusion: Overall, suicide by hanging predominantly involves males of productive age, with asphyxia being the leading mechanism of death.